IRON DEFICIENCY ANEMIA – A RISK FACTOR FOR FEBRILE SEIZURES IN CHILDREN: Iron Deficiency Anemia - Hussain, Abdul Wahid; Haq, Abrar Ul; Shahzad, Sohail; Murtaza, Bilal; Nawaz, Umar; Lodhi, Munir Akmal (Pakistan Armed Forces Medical Journal, 2018)
Objective: To find out the association between iron deficiency anemia and febrile seizures in children. Study Design: Analytical: case-control study. Place and Duration of Study: The study was conducted at Paediatrics department, Pak Emirates Military Hospital Rawalpindi, from May 2013 till Oct 2013. Material and Methods: Two Hundred patients were selected through non probability consecutive sampling, one hundred in each group i.e. patients with febrile seizures and patients without febrile seizures. The blood sample of cases and controls were taken at the time of admission and was sent for assessment of hemoglobin (Hb), serum ferritin level, mean corpuscular hemoglobin concentration (MCHC) and mean corpuscular volume (MCV). The samples were analyzed for iron deficiency anemia and compared in both groups (patients with febrile seizures and those without febrile seizures). Results: In the febrile seizures group 58 (58%) were anemic with a hemoglobin level less than 10gm/dL and 59 (59%) had a low plasma ferritin of less than 10ng/dL. In the control group 39 (39%) were anemic with a hemoglobin level less than 10gm/dL and 26 (26%) had a plasma ferritin of less than 10ng/dL. The frequency of anemia with low MCV, MCHC and serum ferritin was more in the febrile seizure group 38% as compared to 20% in controls (p-value = 0.002). Conclusion: The children with febrile seizures have lower hemoglobin, MCV, MCHC and serum ferritin level as compared to the control groups suggesting that iron deficiency anemia has a positive role in the pathogenesis of febrile seizures.